Muscle oxidative stability, fatty acid and amino acid profiles, and carcass traits of broiler chickens in comparison to spent laying hens - El-Tarabany, Mahmoud S.; Ahmed-Farid, Omar A.; El-Bahy, Salah M.; Nassan, Mohamed A.; Salah, Ayman S. (Frontiers in Veterinary Science, 2022)
This research compared muscle oxidative stability, meat composition, and carcass traits in commercial broilers and spent laying hens. At week 65 of age, 40 ISA Brown laying hens were randomly selected to create 10 replicate cages (4 birds per cage). Also, sixty day-old Ross chicks were equally divided into six replicates (10 chicks each). Broiler chickens had a higher dressing percentage than spent hens (P= 0.027), but a lower abdominal fat percentage (P=0.009). Spent hens had higher level of malondialdehyde (MDA) in the breast muscles (P=0.001). Meanwhile, the MDA levels in thigh muscles did not differ in both groups (P=0.328)..Broiler chickens showed greater concentrations of saturated fatty acids (palmitic and stearic) in the breast (P=0.012 and 0.006, respectively) and thigh (P=0.033 and 0.038, respectively) muscles as compared to spent hens. Meanwhile, broiler chickens had lower concentrations of palmitoleic, oleic and eicosapentaenoic in the breast muscles (P=0.002, 0.004 and 0.001, respectively). Also, spent hens had greater concentrations of linoleic in the breast and thigh muscles (P=0.018 and 0.035, respectively). When compared to broiler chickens, spent hens had greater essential amino acids (isoleucine, methionine and tyrosine) concentrations in the breast muscles (P=0.002, 0.001 and 0.036, respectively). Finally, while broiler chickens had superior carcass traits, spent hens showed better meat composition (higher polyunsaturated fatty acids and essential amino acids). Furthermore, the oxidative stability of the breast muscles of spent hens was lower than that of broilers. Spent hens can be used as an attractive source of chicken meat if certain precautions are adopted.